Making School Happen: Children-Parent-Teacher Collaboration as A Practice of Citizenship - Teresa Sarmento; Ilda Freire (MDPI AG, 2012)
The exercise of citizenship is today understood as a duty and as a right to be enjoyed within any educational context. Within the school, all of its protagonists are invited to exercise practices of citizenship. No one is excluded; even the less important parties have the right to participate in decisions that, for some reason, may have an influence on their academic life. The citizenship of the child is, thus, a challenge to the changing political, social and educational structures, to the transformation of institutions and to cultural renewal. The existence of harmonious relations between the educational community, the school, the children and the family is dependent on everyone's ability to understand and communicate with each other. Parents and teachers have made a commitment to a fruitful and unison dialogue on behalf of the quality of education. In this article, we set out from an analysis of the new social realities and of the different meanings assigned to education, to afterwards reflect upon the current educational values and upon the practices that are consistent with those purposes. Citizenship, as well as autonomy, rise, thus, as central concepts, in which each educational community finds reasons for Making School Happen.